Kontribusi Asupan Zat Gizi Melalui Jalur Enteral, Parenteral Dan Kombinasi Oral Terhadap Pemenuhan Kebutuhan Gizi Pasien Pasca Bedah Digestif Di RSUD Provinsi NTB - Niputu Ayu Devy; Fifi Luthfiyah; inyoman Adiyasa (Poltekkes Kemenkes Mataram, 2018)
Background. On the post digestive surgery patients is has increased metabolic stress as indicated by the increase in energy and protein demand. The feeding for post digestive surgery patients note either through enteral, parenteral and oral combination so that food intake can be given correctly. Research Methods. This study used obeservasional descriptive. The sampling used purposive sampling. Research Result. The all of sample in this research is man which aged over 40 years with hernia inguital lateralis diagnosis and the length of stay postoperative is 3 days. The average of patients intake is 75%, protein 69%, vitamin C 26,33% and kalium 125,3%. The parenteral food that provide to all of sample is ecosol RL infuse as 1000 cc which given when the sample finished the operation. Conclusion. The contribution of energy, protein dan vitamin C only obtained by oral, while the parenteral food is give the contribution of kalium intake as 102,56%.